Multidimensional Analysis of the Green Growth of the European Union Countries in 2019 - Angelika Kantor (Ekonometria)
Green growth is a new approach to the economy that assumes the efficient use of raw materials while minimizing the negative impact on the environment. The aim of the study is to assess green growth in the European Union countries in 2019. For this purpose, secondary data was used and a multidimensional analysis of sustainable development was performed. The non-pattern model together with the Hellwig and Ward methods were implemented. This enabled a comparison between countries, and their classification due to a similar level of development. Based on the analysis, a large discrepancy in terms of green growth was observed in the examined countries. It was noted that the disproportion may turn out to be a problem in the implementation of the sustainable development policy. The results also showed that the position of the country is reflected in its geographic location. (original abstract)